The Phenomenon of Sell in May Effect in the Thai Securities Market - Parkatt, Gallayanee; Pamornmarst, Chayongkan; Thavikitikul, Yothin (The Journal of Development Administration Research, 2024)
The objectives of this study were 1) to study the stock returns in the Thai Securities Market and 2) to investigate Sell in May Effect in the Thai Securities Market. The data used in the study were SET Index for the period from May 1975 to October 2023 and MAI Index for the period from November 2003 to October 2023. The descriptive statistic and the time-series regression were employed to analyse the data. The results reported that; 1) the average monthly return in the Stock Exchange of Thailand (SET) was about 0.74% while those in the Market for Alternative Investment (MAI) was 0.78%. 2) There was no the phenomenon of Sell in May Effect in the Thai securities market. Interestingly, the results informed that April effect appeared in the Thai securities market while the returns in May and December (only in the MAI) were lower than those in the other months, for the period from November 2010 to October 2019, with the statistical significance at 0.05 and 0.10 levels.